Protective Effect of Fluorofenidone Against Acute Lung Injury Through Suppressing the MAPK/NF-κB Pathway - Lv, Xin; Yao, Tingting; He, Rongling; He, Yijun; Li, Mengyu; Han, Yuanyuan; Zhang, Yan; Long, Lingzhi; Jiang, Guoliang; Cheng, Xiaoyun; Xie, Yanyun; Huang, Ling; et al. (Frontiers in Pharmacology, 2021)
Acute lung injury (ALI) is a severe disease that presents serious damage and excessive inflammation in lungs with high mortality without effective pharmacological therapy. Fluorofenidone (AKFPD) is a novel pyridone agent that has anti-fibrosis, anti-inflammation and other pharmacological activities, while the effect of fluorofenidone on ALI is unclarified. Here, we elucidated the protective effects and underlying mechanism of fluorofenidone on lipopolysaccharide (LPS)-induced ALI. In this study, fluorofenidone alleviated lung tissue structure injury and reduced mortality, decreased pulmonary inflammatory cell accumulation and level of inflammatory cytokines IL-1β, IL-6 and TNF-α in bronchoalveolar lavage fluid, attenuated pulmonary apoptosis in LPS-induced ALI mice. Moreover, fluorofenidone could block LPS-activated phosphorylation of ERK, JNK and P38, and further inhibited the phosphorylation of IκB and P65. Theses results suggested that fluorofenidone can significantly contrasted LPS-induced ALI through suppressing the activation of MAPK/NF-κB signaling pathway, which indicates that fluorofenidone could be considered as a novel therapeutics candidate for ALI.